Individual and Collective Reflection: Deepening Early Childhood Pre-service Teachers’ Reflective Thinking during Practicum - Foong, Lydia Yoke Yean; Md Nor, Mariani; Nolan, Andrea (Early Childhood Australia, 2018)
THIS STUDY EXPLORED INDIVIDUAL and collective reflection as pedagogical approaches to support early childhood pre-service teachers’ reflection during practicum. Current trends in the literature show a shift from individual reflection to collective reflection, with an emphasis on social constructivist perspectives. This qualitative study focused on a Malaysian teacher education institution conducting an undergraduate early years program from the UK as the selected case. Sources of evidence came from interviews, direct observations and documents such as student teachers’ teaching portfolios, their reflection journals and assessment forms. The results show that collective reflection supported higher levels of reflective thinking during practicum at the integration, validation and appropriation levels of reflection, compared to when they reflected individually. Collective reflection provided Malaysian teachers with a new platform for problem-solving, connecting theory to practice, as well as the sharing and consideration of multiple perspectives, resulting in a deeper understanding of classroom practices.